Customer perceptions towards the quality of Tmnet Streamyx services offered by Telekom Malaysia (TM) Berhad in Seremban area / Zaid Mat Yusop (Faculty of Business and Management, 2007)
The focus of this study is on the service quality of TMNet Streamyx offered by Telekom Malaysia (TM) Berhad. It is because lately there many complaints made by users about its service. This research also study about how far service dimensions give impact on service quality. By using SERVQUAL, 5 dimensions namely tangibility, reliability, responsiveness, assurance and empathy will be used to evaluate the perceptions of customers towards the service quality of TMNet Streamyx. The research objective is to identify the current level of service quality of TMNet Streamyx services, the factors that influence the service quality of TMNet Streamyx and also to identify the difference of perceptions of service quality among the users of TMNet Streamyx This research use exploratory and descriptive because an exploratory study is undertaken when not much is known about the service quality of TMNet Streamyx services offered by Telekom Malaysia Berhad. While in descriptive research design it would ascertain and to describe the characteristics of the variables of interest in the impact of service quality towards TMNet services. The primary data were gathered through questionnaires distributed in Seremban area.